It’s Gonna Be Alright - Kojnokova, Dana (Slovakia, 2010)
This documentary captures the destiny of two homeless people, it focuses on the issues of people living on the edge of society. Each with a different fate or destiny, motivations and different nature, but with a common goal to get out of the vicious circle. The open ending of the documentary evokes an endless continuity of the vicious circle they are caught up in.
Verzio Film Festival Submission
Keywords: Documentary films